DEFINING THE TERM WALI AL-DAM IN THE LIBYAN LAW OF QISAS AND DIYYA (مجلة أبحاث قانونية, 2023)
According to the Libyan law of Qisas and Diyya, those who determine the penalty for the premeditated murderer are his/her victim’s awliya al-dam; if there is no pardon, the death sentence would be issued, yet if one wali al-dam pardoned, the murderer’s life would be spared and he/she had to bear the penalty of life imprisonment and pay diyya. This essential role of awliya al-dam should have made the legislator accurately define them, and in light of its silence, the author sought through this Paper to determine the scope of wilayat al-dam by limiting its requirements to inheritance, sound mind, and reaching the age of majority at the time of the crime. Therefore, the author believes that the awliya al-dam’s absence at the time of the crime does not affect their right to pardon the offender if they return before execution, but considering the minor heirs are not awliya al-dam should not exclude them from submitting to the rule prohibiting combining the compensation and diyya, because they are entitled to diyya as the victim’s heirs.
Keywords: Wali Al-Dam, Libyan law of Qisas and Diyya; Right to Qisas; Murder; Heirs